(untitled) (Vietnam Journal of Community Medicine, 2024)
Objective: To evaluate the result of arthroscopic anterior cruciate ligament reconstruction with all inside technique in Orthopaedic department - Thong Nhat hospital. Subjects and research Methods: 186 patients with ACL ruptured have arthroscopic surgery in Thong Nhat hospital from 02/2021 to 06/2023, the prospective study. Results: All patients were monitored 1 month, 3 months, 6 months after surgery, evaluated on a Lyshome score, good and very good, reaching 17.75% after 1 month, 87.64% after 3 months. Conclusion: Arthroscopic ACL reconstruction with all inside technique is a new promising method with the advantage of small skin incision, no cavity fracture into bone, large size graft, and tension force.